The effect of Cattle Fat and Coconut Oil on the Blood LDL Cholesterol of the Chicken (Gallus gallus) - Rusli R; M. Nur Salim (Universitas Syiah Kuala, 2007)
This study was conducted to know the influence of cattle fat and coconut oil in affecting bloodLDL cholesterol. Eighteen male local chickens (Gallus gallus) at the age of 2 months were used. Thechickens were allotted into 3 groups of 6 each. The chickens in each groups were fed with 521 standardration (control groups); 9% cattle fat in standard ration 521 (group II); 9% coconut oil in standardration 521 (group III) for 45 days. All chickens were fed ration and drunk ad libitum every day. At theend of the experiment, the blood samples were collected for analysis blood LDL cholesterol withenzymatic methods using spectrophotometre. Analysis of variance with completely randomized designindicated that treatment significantly effect on blood LDL cholesterol (P0.01). From the results could beconcluded that cattle fat 9% supplementation could be increase blood LDL cholesterol levels. While coconut oil supplementation significantly effect on decrease blood LDL cholesterol levels. Keywords: cattle fat, coconut oil, LDL cholesterol